P-Cresol Adsorption And Hemocompatibility Study On Nanoporous Hydroxyapatite - Ooi, Chee Heong (2019)
The present hemodialysis system is ineffective in removing protein-bound uremic toxins, particularly para-cresol (p-cresol) which seriously affects dialysis patients’ health. Thus, it is vital to improve the dialysis process by introducing an effective adsorbent for p-cresol removal in artificial kidney system. Nanoporous hydroxyapatite (HA) is a potential biomaterial for p-cresol removal in artificial kidney system due to its excellent biocompatibility and porosity, which can be optimized via HA synthesis. This study aimed to synthesize nanoporous HA with well-developed porosity and good hemocompatibility targeted for p-cresol removal application. Nanoporous HA was synthesized via hydrothermal method using non-ionic surfactant as soft templates to introduce pores into the biomaterial. The effects of surfactant with different polyethylene-polypropylene (PEO-PPO) unit ratio (i.e., P123 and F127), calcination and surfactant concentration on the pore characteristics of nanoporous HA were investigated. Sodium dodecyl sulfate (SDS) of different concentrations were coated on nanoporous HA as hydrophobic layer to improve the p-cresol removal via hydrophobic interaction. The use of Pluronic P123 and F127 as soft templates in HA synthesis process yielded rod-like HA particles, which agglomerated to form pores. This synthesis method improved the BET surface area of nanoporous HA by 21- 59 % while maintaining the HA phase. The absence of calcination in synthesis process produced HA particles with higher surface area and aspect ratio (length-to-diameter). The increase of surfactant (Pluronic P123) concentration from 6 to 12 and 24 mmol/L resulted in nanoporous HA with better pore characteristics which were desired for achieving a higher p-cresol adsorption capacity. SDS was successfully coated on nanoporous HA at the concentration of 1 and 2 mmol/L. The hemocompatibility of the biomaterial was evaluated via hemolysis test, platelet adhesion, platelet activation and blood clotting time measurement. The results reveal that nanoporous HA is a highly hemocompatible biomaterial and it does not induce any change to blood cells when they are in contact, indicating the feasibility of utilizing the biomaterial in artificial kidney application. p-Cresol adsorption performance was evaluated for nanoporous HA synthesized via different parameters. Nanoporous HA with a larger surface area exhibited better p-cresol adsorption capacity as compared to HA sample with a lower surface area. Pore characteristics are the decisive factors that affect the adsorption performance of nanoporous HA. The SDS coating enhanced the rate constant of p-cresol removal by nanoporous HA. The best p-cresol adsorption performance is shown by nanoporous HA synthesized using P123 at the concentration of 24 mmol/L without going through calcination process and coated with SDS (concentration 4 mmol/L), which is designed as HA-P24-S4 with a p-cresol uptake of 2.45 mg/g.